(untitled) (Research, Society and Development, 2022)
Carbapenem-resistance is a great challenge for antimicrobial therapy in Pseudomonas aeruginosa multidrug-resistant infections, as it reduces therapeutic options. This study investigated carbapenem-resistance mechanisms in six strains of non-carbapenemase-producing P. aeruginosa. Minimal inhibitory concentrations for imipenem and meropenem were determined by epsilometric test and broth microdilution. Mutations in the oprD gene were investigated by PCR, followed by sequencing. Transcriptional levels of oprD, ampC, and efflux pumps genes were analysed through RT-qPCR. Detection of efflux and AmpC activity was assessed by MIC reduction in the presence of the inhibitors: PAβN and cloxacillin, respectively. Resistant strains showed moderate levels of resistance for the evaluated carbapenems. Sequencing of oprD gene revealed similar mutation patterns in strains of the same Sequence Type -ST. A premature stop codon was detected only in the resistant strains of ST2236. Indel mutations were found in the oprD gene of ST2237 strains. Failure to detect oprD transcripts by RT-qPCR further confirms the absence of porin on ST2237 strains. ST2236 strains showed low transcriptional levels for oprD. MexXY-OprM was the only efflux system overexpressed in resistant strains. However, no efflux and AmpC activity was detected. High transcriptional levels of ampC were found in 50% of non-induced resistant strains. All imipem-induced resistant strains showed an increase in ampC expression (>102 - 103 X). It was concluded that the reduction and/or loss of OprD associated with AmpC overexpression is probably the main carbapenem-resistance mechanism in the evaluated strains.